The Relationship Between Oral Health And Psychological Well-Being - Nurfitri Amaliah; Yemy Ameliana; Carera Iva Harryadi (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: People with mental illness often have poor physical health, and this issue has received a lot of attention. However, there has been less focus on the connection between oral health and physical health. This article discusses how oral and mental health are connected. Review: Dental treatment can cause anxiety and phobias. At the same time, many psychiatric disorders, such as severe mental illness, eating disorders, and depression, can lead to dental disease. These include things like caries, periodontitis, and canker sores. Psychotropic drugs, like antidepressants and attention deficit hyperactivity disorder (ADHD) medications, can also cause oral health problems. Many people who get dental work do so while taking these kinds of drugs.  Some of these drugs can cause problems like bruxism (grinding teeth), orofacial dystonia (muscle spasms in the face), oromandibular dyskinesia (uncontrollable movement of the jaw), and rabbit syndrome. These are all related to the way these drugs interact with dopamine receptors in the brain. Furthermore, other pharmaceuticals have been observed to induce xerostomia, a condition characterised by the absence of saliva in the oral cavity. Consequently, patients may be susceptible to infections, including candidiasis, if they do not receive adequate oral hydration. Conclusions: Some potential solutions have been suggested, ranging from the utilisation of standard oral health checklists completed by non-dental personnel to the management of dry mouth induced by medications, and the early referral of patients to dentists.